Sovjetski pogled na zbivanja u Hrvatskoj i Jugoslaviji u drugoj polovini 1950-ih i početkom 1960-ih The Soviet View of the Events in Croatia and Yugoslavia in the Second Half of the 1950s and the Early 1960s - Sokulski, Mateusz (2021)
U članku je analiziran sovjetski pogled na zbivanja u drugoj najvećoj jugoslavenskoj republici tijekom druge polovine 50-ih i prve polovine 60-ih godina. Uzeta je u obzir situacija u Jugoslaviji i međusobni odnosi Beograda i Moskve. Dosad su se povjesničari zanimali prije svega za političku dimenziju međusobnih odnosa i sovjetske ocjene političkoga stanja u Jugoslaviji. Iako su politika i ideologija bile u centru pozornosti sovjetskih diplomata, u članku nisu zanemarena ni kulturna zbivanja u Federativnoj Narodnoj Republici Jugoslaviji (od 1963. Socijalističkoj Federativnoj Republici Jugoslaviji) ni gospodarski položaj zemlje. Ove su dimenzije čvrsto povezivali s političkom sferom te podređivali sovjetskim interesima prema Jugoslaviji. Članak je utemeljen na izvornoj arhivskoj građi prikupljenoj u Moskvi u Ruskom državnom arhivu novije povijesti (Российский государственный архив новейшей истории), u fondu Odjela za veze s komunističkim i radničkim partijama socijalističkih zemalja, koji je odgovarao za odnose sa zemljama komunističkoga uređenja. U radu je korištena i relevantna stručna literatura.
The Soviet view of Croatia, as well as the situation in Yugoslavia, resulted from Soviet interests, its efforts to draw Yugoslavia into its orbit of influence. Particular reluctance was evident on the realm of ideology and purported Western influence, the effectiveness of which was exaggerated in the Soviet documents. In the political dimension, the Kremlin was interested to which extent directives from the center were implemented at the republican level. The attitudes of local politicians toward the actions of the central authorities were also the matter of interest for Soviets. The fact that Croatia was the second richest republic and its aspiration for greater decision-making were regarded as negative phenomenon. Discussions about the competencies of the republics were depicted as closely tied to the national question, referring to the difficult experiences of the first half of the 20th century. In the economic and cultural sphere, there was particular interest in the possibilities of cooperation and building up one's own influence in the Croatian SR. Despite the negative perception of many phenomena in Yugoslav culture, where a critical stance toward the USSR was expressed in film, literature, and the press, Moscow believed that through the presence of Soviet culture - often such as music and theater - it would be possible to gradually gain approval of the public sphere. The Kremlin's propaganda, however, was not as effective in Yugoslavia-as it was throughout the world-as it was in the West. The Soviets paid more attention to events in the center of the country, although they did not ignore regional events either.
Bibliografija
Summary.
Keywords: Sovjetski Savez, Hrvatska, Jugoslavija, ideologija, kultura, propaganda